Passively Q-switched erbium-doped fiber laser based on iron disulfide as a saturable absorber / N. Ahmed … [et al.] - Ahmed, N.; Zulkipli, N.F.; Omar, S.; Jusoh, Z.; Rahman, H.A.; Musa, B.; Harun, S.W. (Universiti Teknologi MARA, 2021)
This work highlights the demonstration of a passively Q-switched pulse laser with iron disulfide (FeS2) as a saturable absorber in near-infrared region. The FeS2 saturable absorber is fabricated using liquid exfoliation method. A small piece of the FeS2-SA film is incorporated into the erbium-doped fiber laser ring cavity resulting in stable repetition rate from 80.4 kHz to 88.5 kHz. The laser delivered a pulse duration that decreases from 12.43 μs to 11.3 μs. By tuning the power pump from 125.2 mW to 166.4 mW, maximum output power and pulse energy are recorded at 2.2 mW and 24.8 nJ respectively. Therefore, this work reveals that FeS2 has good nonlinear saturable absorption properties to produce a stable pulse at 1559.8 nm central wavelength.